The Effect of Whole-body Vibration on Muscle Activity in Active and Inactive Subjects - Lienhard, K.; Vienneau, J.; Friesenbichler, B.; Nigg, S.; Meste, O.; Nigg, B. M.; Colson, S. S. (International Journal of Sports Medicine, 2015)
The purpose of this study was to compare lower limb muscle activity between physically active and inactive individuals during whole-body vibration exercises. Additionally, transmissibility of the vertical acceleration to the head was quantified. 30 active and 28 inactive participants volunteered to stand in a relaxed (20°) and a squat (60°) position on a side-alternating WBV platform that induced vibrations at 16 Hz and 4 mm amplitude. Surface electromyography (sEMG) was measured in selected lower limb muscles and was normalized to the corresponding sEMG recorded during a maximal voluntary contraction. The vertical acceleration on the head was evaluated and divided by the vertical platform acceleration to obtain transmissibility values. Control trials without vibration were also assessed. The outcomes of this study showed that (1) WBV significantly increased muscle activity in the active (absolute increase: +7%, P <0.05) and inactive participants (+8%, P <0.05), (2) with no differences in sEMG increases between the groups (P>0.05). However, (3), transmissibility to the head was greater in the active (0.080) than the inactive participants (0.065, P <0.05). In conclusion, inactive individuals show similar responses in sEMG due to WBV as their active counterparts, but are at lower risk for potential side-effects of vibration exposure.
Keywords: acceleration; surface electromyography; fitness level; inactive population; knee flexion angle